Race and renaissance : African Americans in Pittsburgh since World War II - Day, Jared N., 1963-; Trotter, Joe William, 1945- (UPCC book collections on Project MUSE., 2010)
"This exquisitely researched book is a fine resource for understanding how deindustrialization and urban renewal shaped Black America post-World War II. From these pages emerges a remarkable portrait of a people determined to win full equality and self-determination in spite of mounting obstacles. It is an essential reference for those interested in cities, twentieth-century history, and African American studies."--Mindy Thompson Fullilove, Columbia University.